Overview and different perspectives on possible treatments related to NUT carcinoma: a systematic review - Lopes, Antonia Nayra Gomes; Furtado, Martinho Hermeson de Matos; Silva, Karen Giselly Paulo; Sousa, Lindvaldo de Oliveira; Aguiar, Andrezza Vasconcelos do Vale; Silveira, Giovanni Ciarlini (Brazilian Journal of Oncology, 2019)
NUT carcinoma (midline testicular carcinoma nuclear protein) is a relatively new, rare, aggressive and underdiagnosed entity. Its sites of involvement are medial structures of the head and neck and mediastinum, but other sites may be affected, and even in so-called common structures, the clinical course may impress. The objective of this systematic review was to describe the pathophysiological characteristics of NUT carcinoma and to analyze the types of treatments employed and their efficacy. Throughout the text, treatment - chemotherapy-related forms have been discussed that have led to the complete remission of tumors in some cases, such as the treatment regimen: alternating cycles of vincristine / doxorubicin / ifosfamide and cisplatin / doxorubicin / ifosfamide combined with focal radiotherapy (Scandinavian protocol for inoperable Ewings sarcoma). Other possible future therapies are discussed, in addition to the role of alpha- fetoprotein as a prognostic factor.
Keywords: Carcinoma; Drug Therapy; Medical Oncology.